"HealthKick": Formative assessment of the health environment in low-resource primary schools in the Western Cape Province of South Africa - de Villiers Anniza; Steyn Nelia P; Draper Catherine E; Fourie Jean M; Barkhuizen Gerhard; Lombard Carl J; Dalais Lucinda; Abrahams Zulfa; Lambert Estelle V (BMC, 2012)
Abstract Background This study evaluated the primary school environment in terms of being conducive to good nutrition practices, sufficient physical activity and prevention of nicotine use, with the view of planning a school-based health intervention. Methods A sample of 100 urban and rural disadvantaged schools was randomly selected from two education districts of the Western Cape Education Department, South Africa. A situation analysis, which comprised an interview with the school principal and completion of an observation schedule of the school environment, was done at all schools. Results Schools, on average, had 560 learners and 16 educators. Principals perceived the top health priorities for learners to be an unhealthy diet (50%) and to far lesser degree, lack of physical activity (24%) and underweight (16%). They cited lack of physical activity (33%) and non-communicable diseases (NCDs; 24%) as the main health priorities for educators, while substance abuse (66%) and tobacco use (31%) were prioritised for parents. Main barriers to health promotion programmes included lack of financial resources and too little time in the time table. The most common items sold at the school tuck shops were crisps (100%), and then sweets (96%), while vendors mainly sold sweets (92%), crisps (89%), and ice lollies (38%). Very few schools (8%) had policies governing the type of food items sold at school. Twenty-six of the 100 schools that were visited had vegetable gardens. All schools reported having physical activity and physical education in their time tables, however, not all of them offered this activity outside the class room. Extramural sport offered at schools mainly included athletics, netball, and rugby, with cricket and soccer being offered less frequently. Conclusion The formative findings of this study contribute to the knowledge of key environmental and policy determinants that may play a role in the health behaviour of learners, their parents and their educators. Evidently, these show that school environments are not always conducive to healthy lifestyles. To address the identified determinants relating to learners it is necessary to intervene on the various levels of influence, i.e. parents, educators, and the support systems for the school environment including the curriculum, food available at school, resources for physical activity as well as appropriate policies in this regard.